Reversible energy absorption of elasto-plastic auxetic, hexagonal, and AuxHex structures fabricated by FDM 4D printing - Namvar, N; Zolfagharian, A; Vakili-Tahami, F; Bodaghi, M (Smart materials and structures, 2022)
The present study aims at introducing reconfigurable mechanical metamaterials by utilising four-dimensional (4D) printing process for recoverable energy dissipation and absorption applications with shape memory effects. The architected mechanical metamaterials are designed as a repeating arrangement of re-entrant auxetic, hexagonal, and AuxHex unit-cells and manufactured using 3D printing fused deposition modelling process. The AuxHex cellular structure is composed of auxetic re-entrant and hexagonal components. Architected cellular metamaterials are developed based on a comprehension of the elasto-plastic features of shape memory polylactic acid materials and cold programming deduced from theory and experiments. Computational models based on ABAQUS/Standard are used to simulate the mechanical properties of the 4D-printed mechanical metamaterials under quasi-static uniaxial compression loading, and the results are validated by experimental data. Research trials show that metamaterial with re-entrant auxetic unit-cells has better energy absorption capability compared to the other structures studied in this paper, mainly because of the unique deformation mechanisms of unit-cells. It is shown that mechanical metamaterials with elasto-plastic behaviors exhibit mechanical hysteresis and energy dissipation when undergoing a loading-unloading cycle. It is experimentally revealed that the residual plastic strain and dissipation processes induced by cold programming are completely reversible through simple heating. The results and concepts presented in this work can potentially be useful towards 4D printing reconfigurable cellular structures for reversible energy absorption and dissipation engineering applications.